Training on Environmentally Friendly Technology for Processing Tofu Waste for MSMEs in Yogyakarta - Liya Yusrina Sabila; Shinta Amelia; Rachma Tia Evitasari; Irvanda Cheza Noor Fadhilla; Fakhra Kurnia Yasa; Ninda Nurul Fatikha (UKInstitute, 2026)
Micro, Small, and Medium Enterprises (MSMEs) producing tofu play an important role in the national economy, but most of them have not properly managed their production waste, which has the potential to cause environmental pollution. This community service activity aims to implement a simple, effective, and sustainable tofu liquid waste treatment technology, as well as to enhance the human resource capacity of MSME partners in Yogyakarta to manage waste independently. The methods used include observation, in-depth interviews, questionnaires, and the implementation of four outreach sub-activities: (1) the hazards of tofu waste content, (2) wastewater quality standards, (3) wastewater treatment methods, and (4) Internet of Things (IoT)-based waste treatment technology. The results of the activity show that more than 80% of the partners have been educated about the dangers of waste, understand the correct treatment methods, and are able to use IoT technology to monitor waste parameters in real-time via smartphones. The impact of this community service is an increase in partners' awareness of environmental responsibility and their readiness to implement sustainable waste treatment technology.